2005
DOI: 10.1194/jlr.d400030-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex ligation-dependent probe amplification of LDLR enhances molecular diagnosis of familial hypercholesterolemia

Abstract: Autosomal dominant (AD) familial hypercholesterolemia [FH; Mendelian Inheritance in Man (MIM) 143890]typically results from mutations in the LDL receptor gene ( LDLR ), which are now commonly diagnosed using exon-byexon screening methods, such as exon-by-exon sequence analysis (EBESA) of genomic DNA (gDNA). However, many patients with FH have no LDLR mutation identified by this method. Part of the diagnostic gap is attributable to the genetic heterogeneity of AD FH, but another possible explanation is inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 17 publications
2
48
0
1
Order By: Relevance
“…The probands were reported to have an unusual phenotype of aggravated hypercholesterolaemia that was complicated with premature coronary arterial disease, although remaining responsive to The case we present in this paper is a double heterozygote for the p.Leu479Pro mutation in the LDLR gene and the common p.Arg3527Gln mutation in the APOB gene. The p.Leu479Pro mutation has been reported previously, 5,14,15 and we have found this mutation in 4/414 ( 1%) of our unrelated patients with detected mutations. Although no functional studies have been performed to confirm its pathogenicity, the p.Leu479Pro mutation occurs in the epidermal growth factor spacer domain of the LDLR protein that is required for acid-dependent dissociation of the receptor from its ligand during recycling, and the mutation may interfere with receptor recycling.…”
Section: Discussionmentioning
confidence: 79%
“…The probands were reported to have an unusual phenotype of aggravated hypercholesterolaemia that was complicated with premature coronary arterial disease, although remaining responsive to The case we present in this paper is a double heterozygote for the p.Leu479Pro mutation in the LDLR gene and the common p.Arg3527Gln mutation in the APOB gene. The p.Leu479Pro mutation has been reported previously, 5,14,15 and we have found this mutation in 4/414 ( 1%) of our unrelated patients with detected mutations. Although no functional studies have been performed to confirm its pathogenicity, the p.Leu479Pro mutation occurs in the epidermal growth factor spacer domain of the LDLR protein that is required for acid-dependent dissociation of the receptor from its ligand during recycling, and the mutation may interfere with receptor recycling.…”
Section: Discussionmentioning
confidence: 79%
“…One of the large deletions was found in one family with a severe phenotype ( Supplementary Fig. S2); a 5-year-old girl and her father with premature CHD carried the same allele with a deletion of the 3 -end of the LDLR gene comprising exons [16][17][18]. The other large deletion, of exons 2 and 3, was found in a child, his brother and father with a severe phenotype and a family history of premature CHD.…”
Section: Ldlr Genementioning
confidence: 98%
“…For instance, we recently showed that testing for both SNPs and CNVs expands the molecular diagnosis of familial hypercholesterolemia. 39 Like SNPs, smaller CNVs will affect only single genes and thus contribute, together with SNPs, to single-gene disorders. However, unlike SNPs, larger CNVs can affect 2 or more contiguous genes and thus contribute to syndromic or complex disorders caused by defects in multiple genes.…”
Section: How Do Cnvs Cause Disease or Influence Phenotypes?mentioning
confidence: 99%